"I Solemnly Swear that I Am up to No Good": Mapping My Way through TESOL Teacher Education. Issue 1 (2nd January 2019) - Thomas, M'Balia
ABSTRACT: This article documents my 2-year sojourn from voicelessness – in the face of normalizing discourses about race, privilege, and difference in teacher education scholarship – to an authentic voice capable of addressing normalizing discourses from a position of inclusivity. This journey has involved my face-to-face and even mediated engagement with a critical community of human scholars. In difference to most self-study work, it has included my dialogic engagement with literary (Audre Lorde and Gloria Anzaldúa) and popular (J. K. Rowling's Harry Potter series) textual critical partners. In highlighting the role of these textual partners in my self-study research, I draw upon the field of cognitive poetics and reader response theory to push against the boundaries of self-study practice and methodology.